Automated SARS-COV-2 RNA extraction from patient nasopharyngeal samples using a modified DNA extraction kit for high throughput testing - Al-Saud, Haya; Al-Romaih, Khaldoun; Bakheet, Razan; Mahmoud, Lina; Al-Harbi, Najla; Alshareef, Ibtihaj; Judia, Sara Bin; Aharbi, Layla; Alzayed, Abdulaziz; Jabaan, Amjad; Alhadrami, Hani; Albarrag, Ahmed; et al. (Annals of Saudi medicine, 2020)
The pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) has prompted a need for mass testing to identify patients with viral infection. The high demand has created a global bottleneck in testing capacity, which prompted us to modify available resources to extract viral RNA and perform reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) to detect SARS-COV-2. Report on the use of a DNA extraction kit, after modifications, to extract viral RNA that could then be detected using an FDA-approved SARS-COV-2 RT-qPCR assay. Initially, automated RNA extraction was performed using a modified DNA kit on samples from control subjects, a bacteriophage, and an RNA virus. We then verified the automated extraction using the modified kit to detect in-lab propagated SARSCOV-2 titrations using an FDA approved commercial kit (S, N, and ORF1b genes) and an in-house primer-probe based assay (E, RdRp2 and RdRp4 genes). Automated RNA extraction on serial dilutions SARS-COV-2 achieved successful one-step RT-qPCR detection down to 60 copies using the commercial kit assay and less than 30 copies using the in-house primer-probe assay. Moreover, RT-qPCR detection was successful after automated RNA extraction using this modified protocol on 12 patient samples of SARS-COV-2 collected by nasopharyngeal swabs and stored in viral transport media. We demonstrated the capacity of a modified DNA extraction kit for automated viral RNA extraction and detection using a platform that is suitable for mass testing. Small patient sample size. None.